Pesticide Research Trend With Bibliometric Analysis - Maharani, Nine Elissa; Anggoro, Sutrisno; ., Nurjazuli (South Eastern European Journal of Public Health, 2024)
Pesticide use increased significantly in 1940. Human exposure to pesticides can occur through consumption of contaminated food or water, inhalation of contaminated air and skin contact with contaminated water, air, food or soil. Using pesticides that do not meet standards will cause health problems, environmental pollution and disrupt the ecosystem. The aim of this research is to analyze publication trends regarding the impact of pesticides on the environment and health. The method used is bibliometric analysis using VOSviewer visualization. The data comes from Scopus on the topic of pesticides and their impact on the environment and health from 1975 to 2024. Data from Scopus must be exported and then screened first so that there are no duplicate keywords. The total number of articles analyzed from 1975 to 2024 was 7,478 articles. The keyword that appears most often is pesticide with a total link strength of 454. The results of bibliometric analysis using the VOS viewer showed 11 clusters. Each cluster consists of several keyword items. The most frequently appearing keyword, namely pesticide, is in cluster 4. The trend of publications about pesticides increased sharply from 2021 to 2024. The highest number of publications was in 2023, namely 849 articles. The language used in article publication is mostly English with the publisher Elsevier. . The most cited article is the article with the title Pharmaceuticals And Personal Care Products In The Environment: Agents Of Subtle Change?. The authors of the article are Daughton, Christian G. ; Ternes, Thomas A. The number of citations from this author is 4024.